Smart Libraries for Smart Age: Exploring the Future of Libraries in the Smart Age (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the smart age, idea of the smart library means different things to different users. Smart libraries will be dependent on the skills of the librarians as well as transformational impact of the integrated learning. Role of future librarians will be governed by the technology of Automation, Digitization, immersive technologies like AI, VR, IoT, Robotics etc. The paper is highlighting the Digital Learning (DL) and Machine Learning (ML) since the librarians are working as a conduit for digital capabilities. Outlines of new concept of smart libraries can be described in four dimensions such as smart governance, smart services, smart place and smart people. The smart library concept does not constitute a unique model or project but a process, a way of how to get things done that is less linear, less structured and more creative and innovative. The paper concludes that in smart age the libraries are harnessing the power of new technologies and they are the melt pot of ideas.